1997
DOI: 10.2337/diacare.20.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Therapy of IDDM With an Implantable Insulin Pump

Abstract: Long-term implantable pump therapy maintained HbA1c in a range similar to intensive subcutaneous therapy, but with fewer episodes of severe hypoglycemia. Although pump and catheter occlusions remain a limitation, patient satisfaction with implantable pump therapy remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…The intraperitoneal insulin infusion pump has shown improvements in QOL compared to standard insulin pump treatment[105, 106], although the comparative impact on HbA1c remains unclear[106, 107]. Inhaled insulin has also shown improvements in glycemic control and treatment satisfaction in a randomized controlled trial with adult type 1 diabetes patients[108, 109].…”
Section: Impact Of Diabetes Technology On Quality Of Lifementioning
confidence: 99%
“…The intraperitoneal insulin infusion pump has shown improvements in QOL compared to standard insulin pump treatment[105, 106], although the comparative impact on HbA1c remains unclear[106, 107]. Inhaled insulin has also shown improvements in glycemic control and treatment satisfaction in a randomized controlled trial with adult type 1 diabetes patients[108, 109].…”
Section: Impact Of Diabetes Technology On Quality Of Lifementioning
confidence: 99%
“…Its safety and efficacy has been reported by the Evaluation of Active Implants in Diabetes (EVADIAC) study group and others [1][2][3][4][5][6]. Better glycaemic control in terms of lower HbA 1c , decreased number of hypoglycaemic events and reduced glycaemic variability can be achieved and patients' treatment satisfaction is high [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 95%
“…The description of the Infusaid Model 1000 pump (Strato/Infusaid, Norwood, MA) and the results of the clinical trial in patients with type I diabetes are reported elsewhere (2,5). The device is implanted in a subcutaneous pocket created within the abdominal wall and attached to the fascia.…”
Section: Methods-mentioning
confidence: 99%
“…D uring insulin therapy using an implanted pump, catheter complications are observed with both intraperitoneal and intravenous delivery (1)(2)(3)(4)(5)(6)(7). Occlusions, caused by deposition of insulin aggregates inside the lumen and by fibrous tissue growth or clotting at the tip and inside the distal end, are the most frequent catheter complications (8)(9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation